Characterization of trench Schottky diode with trench bottom oxide (TBO) process: article / Nurul Izzati Mohammad Noh, Mohd Rofei Mat Hussin and Maizatul Zolkapli - Mohammad Noh, Nurul Izzati; Mat Hussin, Mohd Rofei; Zolkapli, Maizatul (2012)
A new Schottky diode structure namely as TBO Trench Schottky diode is proposed. Introduction of TBO process to the trench Schottky diode has shown better device characteristics. In this study, the trench bottom oxide (TBO) process was developed in order to increased reverse blocking voltage of Schottky diode. As a result from the study, an improved reverse blocking voltage has been achieved. TBO layer in trench structure can reduce the electric field crowding at the corner of trench bottom then increased the breakdown voltage as shown in Fig. 1 and Fig. 4. From experimental results, breakdown voltage for Schottky diode structure with TBO is about -64.50V whereas the Schottky diode structure without TBO is around -60.50V. There is about 4V difference of breakdown voltage due to TBO effect. Another important factor that also determines the breakdown voltage of Schottky diode is gate oxide thickness. Thicker gate oxide demonstrating higher breakdown voltage.